2009
DOI: 10.1148/rg.293085093
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic Complications of Liver Cirrhosis: Radiologic Findings

Abstract: Patients with chronic liver disease exhibit various cardiovascular and pulmonary complications. Hepatopulmonary syndrome results in dyspnea due to intrapulmonary arteriovenous shunting and ventilation-perfusion mismatch. Portopulmonary hypertension occurs in patients with portal hypertension. Intrathoracic portosystemic collateral vascular pathways develop in patients with portal hypertension to allow decompression of the portal vein into the systemic circulation. Hepatic hydrothorax may develop in patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 47 publications
3
21
0
2
Order By: Relevance
“…2A). 30,31 Findings suggestive of pulmonary hypertension on CT of the chest include increased pulmonary artery diameter, particularly if it is greater than the diameter of the aorta, and increased segmental artery-to-bronchus ratios in multiple pulmonary lobes (Figs. 2B, C).…”
Section: Radiologic Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…2A). 30,31 Findings suggestive of pulmonary hypertension on CT of the chest include increased pulmonary artery diameter, particularly if it is greater than the diameter of the aorta, and increased segmental artery-to-bronchus ratios in multiple pulmonary lobes (Figs. 2B, C).…”
Section: Radiologic Studiesmentioning
confidence: 99%
“…Lung perfusion testing may also show multiple patchy defects in the setting of severe pulmonary hypertension. 31 Electrocardiography Abnormal electrocardiogram findings most commonly associated with POPH include right ventricular hypertrophy and right axis deviation. 30 Right and left atrial abnormality or enlargement, right bundle branch block and first-degree atrioventricular block may also be seen.…”
Section: Radiologic Studiesmentioning
confidence: 99%
“…The prevalence of hepatopulmonary syndrome in adult cirrhotic patients ranges between 15-20% [1]. Krowka et al, found that dyspnea is the presenting symptom in 18% of the patients [3].…”
Section: Discussionmentioning
confidence: 99%
“…The most common type (type 1), which includes 86% of the patients, is characterized by subpleural telangiectasia and peripheral vascular dilatation. Type 2 hepatopulmonary syndrome (14% of patients) is characterized by arteriovenous malformations and nodular dilatations in peripheral pulmonary arteries [1,3,7]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation